Monitoring good practices in the areas of employment, social affairs and inclusion. Report on examples of projects funded by DG EMPL in 2012-2015 - volume 4 (Luxembourg, 2016)
"This monitoring report gathers good practices of projects across Europe dealing with working conditions, employment, social affairs and inclusion. One of the selected projects is "The job of my life" project, supporting young persons from Europe in finding an in-house vocational training position in Germany. Another example of good practice is a French project which created info points in selected schools to prepare future graduates integrate the labour market. All selected project were supported by the EURES financial instrument or by the PROGRESS programme."